Highly selective separation of eucalyptus hemicellulose by salicylic acid treatment with both aromatic and hydroxy acids. (July 2022) - Deng, Baojuan; Hou, Yajun; Wang, Fei; Bao, Yuqi; Zeng, Fanyan; Qin, Chengrong; Liang, Chen; Huang, Caoxing; Ma, Jiliang; Yao, Shuangquan
Graphical abstract: Highlights: Hemicellulose was separated efficiently by salicylic acid treatment. The separation yield of xylose was 85.93%. The extraction yield of lignin decreased to 12.36%. The separation of aromatic and hydroxyl acids treatment was combined. Abstract: Aromatic and hydroxyl acid treatments demonstrate their respective characteristics for the separation of lignocellulosic biomass. In this study, the effect of salicylic acid (SA-A) treatment on the separation of eucalyptus components with both aromatic and hydroxyl acid properties was analyzed. The optimal conditions were SA-A concentration 9.0%, reaction temperature 140 °C and time 75 min. The separation yield of xylose was 85.93%. The separation of cellulose and lignin was inhibited by SA-A treatment in contrast to the separation by glycolic acid and p -toluenesulfonic acid treatment. Moreover, SA-A treatment resulted in a larger fiber crystallinity index and higher thermal stability. The SA-A-treated samples contained lignin that was rich in β-O-4 and hydroxyl groups. The degradation and condensation of lignin was inhibited. The selectivity of aromatic acids for separating hemicellulose and protecting the lignin structure using hydroxy acids was demonstrated. Thus, new and efficient organic acid treatments can be developed.